2005
DOI: 10.1111/j.1460-9568.2004.03843.x
|View full text |Cite
|
Sign up to set email alerts
|

Neocortex is the major target of sedative concentrations of volatile anaesthetics: strong depression of firing rates and increase of GABAA receptor‐mediated inhibition

Abstract: General anaesthetics cause sedation, amnesia and hypnosis. Although these clinically desired actions are indicative of an impairment of neocortical information processing, it is widely held that they are to a large part mediated by subcortical neural networks. Anaesthetic action on brain stem, basal forebrain and thalamus, all of which are known to modulate cortical excitability, would thus ultimately converge on neocortex, perturbing and reducing action potential activity therein. However, as neocortex harbou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
99
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 164 publications
(108 citation statements)
references
References 59 publications
9
99
0
Order By: Relevance
“…Studies conducted in the future comparing the effects of conventional stressors and FG-7142 on the functional connectivity between mPFC and BLA will be useful to confirm the validity of using FG-7142 to model the effects of stress on corticolimbic network interactions. The effects of isoflurane, the anesthetic used in the present study, are mediated in part by potentiating cortical (Hentschke et al, 2005) and amygdaloid (Ranft et al, 2004) GABA A receptor function, the site of benzodiazepine binding and action of FG-7142 and FLU. Thus, future experiments conducted in the freely-behaving animal will avoid the potential confound of drug interactions between isoflurane, FG-7142 and/or FLU.…”
Section: Discussionmentioning
confidence: 93%
“…Studies conducted in the future comparing the effects of conventional stressors and FG-7142 on the functional connectivity between mPFC and BLA will be useful to confirm the validity of using FG-7142 to model the effects of stress on corticolimbic network interactions. The effects of isoflurane, the anesthetic used in the present study, are mediated in part by potentiating cortical (Hentschke et al, 2005) and amygdaloid (Ranft et al, 2004) GABA A receptor function, the site of benzodiazepine binding and action of FG-7142 and FLU. Thus, future experiments conducted in the freely-behaving animal will avoid the potential confound of drug interactions between isoflurane, FG-7142 and/or FLU.…”
Section: Discussionmentioning
confidence: 93%
“…The disappearance of the notch does not exclude additional involvement of facilitatory mechanisms acting on longer timescales (42) and changing excitation-inhibition balance in favor of LTP-like excitation. Additionally, volatile anesthesia as used here reduces spontaneous activity and increases inhibition (66). Hence, the excitatory levels found after high-frequency stimulation might be underestimated, whereas notch strength before TMS might be overestimated.…”
Section: Discussionmentioning
confidence: 94%
“…Certainly, cortical neurons are sensitive to general anesthetics, 62,63 and cortical inhibition could influence thalamic activity via the descending corticofugal pathway. 64 A study that concluded that cortical changes in the EEG preceded changes in thalamic local field potentials at loss of consciousness supports this view but, interestingly, a recent study concluded the opposite during sleep onset.…”
Section: Sleep and General Anesthesia 143mentioning
confidence: 99%